Jewish theatre : a global view - Nahshon, Edna (IJS studies in Judaica ;, 2009)
In this valuable contribution to Jewish studies, Nahshon (Hebrew, Jewish Theological Seminary, New York) addresses the question of what defines 'Jewish theatre' and its audience in her introduction to the volume's other 15 essays. International contributors treat the themes of theatre by Jews for Jews produced in Yiddish, theatre by Jews for a broader Polish audience, Jewish presentations in different languages, American Jewish identity in American theatre, and dramatic engagements with the Holocaust and modern Israel on the Israeli stage. A monologue by the biblical character of Abraham is ap.